Investigation of High Temperature Wear and Cyclic Oxidation Behavior of Pack-Aluminized Inconel 601 - Doleker, Kadir Mert; Oge, Tuba Ozdemir; Oge, Mecit; Ak, Sevket; Kucuk, Yilmaz; Gunen, Ali; Gok, Mustafa Sabri (Elsevier Science Sa, 2025)
IN601 (Inconel 601) superalloy sample surfaces were subjected to pack-aluminizing heat treatment at 700 degrees C for 4-h treatment period. The microstructural changes in the produced samples were assessed with scanning electron microscopy (SEM) and the phase structures of the treated surfaces were studied with X-ray diffractometry (XRD). To investigate the effect of thermochemical surface hardening on the high temperature tribological performance of the produced samples, dry sliding pin-on-disc wear tests were performed at room temperature and 400 degrees C under 7 N and 15 N loads. Microhardness and nano hardness measurements were also performed on the sample cross-sections. High temperature wear tests showed that, thermochemical surface hardening reduced the specific wear rates by nearly 39 %, 38 %, 49 % and 51 % under room temperature and 7 N, room temperature and 15 N, 400 degrees C and 7 N, and 400 degrees C and 15 N, respectively. Heat treatment enhanced the microhardness and nano hardness of the samples by nearly 382 % and 394 %, respectively. The enhancement of wear performance and hardness values is mainly attributed to the formation of hard aluminide phases after heat treatment. Cyclic oxidation tests were performed at 1000 degrees C in 10-h cycles amounting to a total of 50 h. Despite the formation of local damages within the oxide layer, the persistent presence of the alumina layer in aluminized IN601 forming after the oxidation cycles significantly improved the oxidation resistance as the rate constants for were calculated as 0.0013 mg1.86.cm-3.71 and 0.0173 mg1.94.cm-3.87 for aluminized IN601 and bare IN601, respectively.
Doleker, Kadir Mert/0000-0003-4057-6832;
Keywords: Aluminizing; Inconel 601; High Temperature Wear; Hardness; Cyclic High Temperature Oxidation